Avaliação do Programa “Novo Rio Pinheiros” a partir da percepção dos usuários do Parque Linear Bruno Covas - Luizatto Filho, Romeu (Universidade Federal de São Carlos, 2025)
The process of disorderly urbanization in large Brazilian cities has caused significant environmental changes, particularly in urban water systems. In São Paulo, territorial expansion and industrialization have profoundly altered the natural dynamics of the Pinheiros River, resulting in rectifications, canalizations, and high levels of pollution. Given this scenario, in 2019, the São Paulo State Government instituted the “Novo Rio Pinheiros” Program, aimed at cleaning up and revitalizing its banks, integrating actions in sanitation, infrastructure, leisure, mobility, and environmental education. This dissertation evaluates the program as a public policy, based on the perception of users of the riverbanks, analyzing the relationship between the daily use of the space and the perception of its environmental and social impacts. This is an exploratory and descriptive study, with a qualitative and quantitative approach, conducted with 196 visitors to the Bruno Covas Linear Park – Novo Rio Pinheiros, using a structured questionnaire. The data were analyzed using descriptive and multivariate statistical techniques. The results indicate the existence of different profiles of environmental perception and evaluation of the program, highlighting the appreciation of revitalization actions and the symbolic reconnection with the river, although challenges remain regarding the effective recovery of water quality and the sustainability of interventions. The study highlights the relevance of social perception and citizen participation in assessing the effectiveness and legitimacy of public environmental policies.
Evaluation of the “Novo Rio Pinheiros” Program based on the perception of users of the Bruno Covas Linear Park
Keywords: Revitalização de Rios Urbanos; Rio Pinheiros; Percepção Ambiental; Sustentabilidade; Urban River Revitalization; Pinheiros River; Environmental Perception; Sustainability; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; OUTROS::CIENCIAS SOCIAIS; 6. Água Potável e Saneamento; 11. Cidades e Comunidades Sustentáveis; 14. Vida na Água; 15. Vida Terrestre